Interpersonal Servant Communication Relationship With Buyer Satisfaction of Resto Ayam Jingkrak Tanjung Balai - Hakiki, Fitri; Sikumbang, Ahmad Tamrin; Harahap, Suheri (Pena Cendekia Insani, 2023)
This study aims to determine whether there is a relationship between interpersonal communication between waiters and customer satisfaction at Jingktak Chicken Resto. The theory used in this study is the theory of interpersonal communication, and the theory of buyer satisfaction. The research method used is a correlational quantitative research method that seeks the relationship between variable X (interpersonal communication of waiters) and variable Y (with buyer satisfaction). Correlational method is a method that aims to determine the relationship of a variable with other variables. The sampling technique used was purposive sampling and accidental sampling. The researcher first determines the criteria for respondents and then selects respondents who coincidentally meet and match these characteristics. The population in this study were buyers of the Tanjungbalai Jingkrak Chicken Restaurant. Based on the sample calculation using the Slovin formula, a total sample of 97 people was obtained. In this study, the samples were buyers who visited the Jingkrak Chicken Restaurant, Tanjungbalai. Data collection techniques were carried out in this study in three ways, namely observation by going directly to the field, questionnaires by distributing questionnaires, and documentation. Data analysis techniques used in this study were single table analysis, cross table analysis, and hypothesis testing through the Correlation Coefficient formula by Spearman using the SPSS 26 application. The results of this study obtained a correlation coefficient of 0.564. Based on the Guilford scale used, the coefficient shows a significant relationship between interpersonal communication between waiters and customer satisfaction at Prancing Chicken Resto. Then the result of the coefficient of determination is 31.8%, the factor that influences the interpersonal communication relationship between the waiter and the buyer's satisfaction, while 68.2% is influenced by other factors.